A geometry problem by Jose Sacramento

Geometry Level 3


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Michael Huang
Dec 2, 2016

Relevant wiki: Fundamental Trigonometric Identities - Problem Solving (Easy)

Section I. Equation A

By complementary angle identities , cos ( π 22 ) = sin ( π 2 π 22 ) = sin ( 5 π 11 ) cos ( 7 π 12 ) = sin ( 7 π 12 π 2 ) = sin ( π 12 ) \begin{array}{rl} {\color{#20A900}\cos\left(\dfrac{\pi}{22}\right)} &= \sin\left(\dfrac{\pi}{2} - \dfrac{\pi}{22}\right) = {\color{#20A900}\sin\left(\dfrac{5\pi}{11}\right)}\\ {\color{#3D99F6}\cos\left(\dfrac{7\pi}{12}\right)} &= \sin\left(\dfrac{7\pi}{12} - \dfrac{\pi}{2}\right) = {\color{#3D99F6}\sin\left(\dfrac{\pi}{12}\right)} \end{array} Applying the following Pythagorean identity sin 2 ( θ ) + cos 2 ( θ ) = 1 \sin^2\left(\theta\right) + \cos^2\left(\theta\right) = 1 gives A = cos 2 ( 5 π 11 ) + cos 2 ( π 22 ) + cos 2 ( 7 π 12 ) + cos 2 ( π 12 ) = 1 + 1 = 2 \begin{array}{rl} A = \cos^2\left(\dfrac{5\pi}{11}\right) + {\color{#20A900}\cos^2\left(\dfrac{\pi}{22}\right)} + {\color{#3D99F6}\cos^2\left(\dfrac{7\pi}{12}\right)} + \cos^2\left(\dfrac{\pi}{12}\right) = 1 + 1 = 2 \end{array}


Section II. Equation B

Since 14 π 9 , 13 π 9 π \dfrac{14\pi}{9}, \dfrac{13\pi}{9} \geq \pi , sin < 0 \sin < 0 . In this case, express sin ( 14 π 9 ) = sin ( 14 π 9 π ) = sin ( 5 π 9 ) sin ( 13 π 9 ) = sin ( 13 π 9 π ) = sin ( 4 π 9 ) \begin{array}{rl} {\color{#D61F06}\sin\left(\dfrac{14\pi}{9}\right)} &= -\sin\left(\dfrac{14\pi}{9} - \pi\right) = {\color{#D61F06}-\sin\left(\dfrac{5\pi}{9}\right)}\\ {\color{#69047E}\sin\left(\dfrac{13\pi}{9}\right)} &= -\sin\left(\dfrac{13\pi}{9} - \pi\right) = {\color{#69047E}-\sin\left(\dfrac{4\pi}{9}\right)} \end{array} which yield B = ( sin ( 4 π 9 ) + sin ( 14 π 9 ) ) + ( sin ( 5 π 9 ) + sin ( 13 π 9 ) ) = 0 \begin{array}{rl} B &= \left(\sin\left(\dfrac{4\pi}{9}\right) + {\color{#D61F06}\sin\left(\dfrac{14\pi}{9}\right)}\right) + \left(\sin\left(\dfrac{5\pi}{9}\right) + {\color{#69047E}\sin\left(\dfrac{13\pi}{9}\right)}\right)\\ &= 0 \end{array}


Section III. Equation C

Observe that cos ( 14 π 25 ) = cos ( 11 π 25 ) \begin{array}{rl} \cos\left(\dfrac{14\pi}{25}\right) &= -\cos\left(\dfrac{11\pi}{25}\right) \end{array} and cos ( 15 π 26 ) = sin ( 15 π 26 π ) = sin ( π 13 ) \begin{array}{rl} \cos\left(\dfrac{15\pi}{26}\right) &= -\sin\left(\dfrac{15\pi}{26} - \pi\right) = -\sin\left(\dfrac{\pi}{13}\right)\\ \end{array} Then, C = ( sin ( π 13 ) + cos ( 15 π 26 ) ) + ( cos ( 11 π 25 ) + cos ( 14 π 25 ) ) = 0 C = \left(\sin\left(\dfrac{\pi}{13}\right) + \cos\left(\dfrac{15\pi}{26}\right)\right) + \left(\cos\left(\dfrac{11\pi}{25}\right) +\cos\left(\dfrac{14\pi}{25}\right)\right) = 0


Section IV. Answer

Therefore, A + B + C = 2 A + B+ C = \boxed{2} .

Very clear explanations for these sums :)

In this case, they only look scary, but are succumb to the basic properties.

Calvin Lin Staff - 4 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...